Despite reproductive interference, the net outcome of reproductive interactions among spider mite species is not necessarily costly. (22nd December 2017) - Clemente, Salomé H; Santos, Inês; Ponce, Rita; Rodrigues, Leonor R; Varela, Susana A M; Magalhães, Sara
Abstract : Some closely-related species have reproductive interactions between them. Here, we show that the outcome of such interactions is highly variable. We did crosses among 3 species of herbivorous spider mites that co-occur in the Mediterranean and found that, depending on the order and timings of matings, they could be negative, neutral or positive. Therefore, the study of such interactions needs to account for the details of mating events, as the devil may be in them! Abstract: Reproductive interference is considered a strong ecological force, potentially leading to species exclusion. This supposes that the net effect of reproductive interactions is strongly negative for one, or both, of the species involved. Testing this requires a comprehensive analysis of interspecific reproductive interactions, accounting for the order and timing of mating events, and for their effects on either fertility or fecundity. To this aim, we measured reproductive interactions among spider mites, using a focal species, Tetranychus urticae, and an invasive ( T. evansi ) and a resident ( T. ludeni ) species, varying the mating sequence and interval, and measuring the effect of such crosses on fecundity and offspring sex ratio (a measure of fertility, as these species are haplodiploid). We found that mating with heterospecifics affected fecundity and sex ratio negatively or positively, depending on the species involved, and on the order and timing of mating events. Overall, the net effect of reproductive interactions was weak despite strong effects of particular events. In natural situations, the outcome of reproductive interactions will thus hinge upon the frequency of each event.